Graphene Nanoribbons 2019
DOI: 10.1088/978-0-7503-1701-6ch4
|View full text |Cite
|
Sign up to set email alerts
|

Emergent quantum matter in graphene nanoribbons

Abstract: In this book chapter, we introduce different schemes to create quantum states of matter in engineered graphene nanoribbons. We will focus on the emergence of controllable magnetic interactions, topological quantum magnets, and the interplay of magnetism and superconductivity. We comment on the experimental signatures of those states stemming from their electronic and spin excitations, that can be observed with atomic resolution using scanning probe techniques. arXiv:1909.00258v3 [cond-mat.mes-hall]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Although electronic correlations are expected to play a crucial role for the localized topological states in GNR heterostructures, so far, most theoretical work has been restricted to tight-binding (TB) models or density functional theory within the local density approximation (LDA-DFT), which are known to completely ignore or underestimate these effects. Here, we present a systematic analysis of electronic correlations in 7–9-AGNRs, based on a Green functions method with GW self-energy , applied to an effective Hubbard model.…”
mentioning
confidence: 99%
“…Although electronic correlations are expected to play a crucial role for the localized topological states in GNR heterostructures, so far, most theoretical work has been restricted to tight-binding (TB) models or density functional theory within the local density approximation (LDA-DFT), which are known to completely ignore or underestimate these effects. Here, we present a systematic analysis of electronic correlations in 7–9-AGNRs, based on a Green functions method with GW self-energy , applied to an effective Hubbard model.…”
mentioning
confidence: 99%
“…(This is different from the well studied CrI 3 monolayer, where the Cr 3+ ion has a closed t 3 2g shell and has a negligible SIA, and the notable anisotropic exchange comes from the strong SOC of the heavy I 5p orbitals and strong Cr 3d-I 5p hybridization. 19,20 ) Note that for VBr 3 monolayer under the tensile strain, the FM J parameter is significantly enhanced, and the SIA D parameter changes from a small negative value to a large positive one, see the bare VBr 3 monolayer, its T C is about 20 K, according to our Monte Carlo simulations, due to the relatively small SIA and the relatively weak FM superexchange. In strong contrast, the VBr 3 monolayer has a significantly increasing T C up to 100-115 K under the 2.5-5% tensile strain, due to the strong FM coupling and strong SIA.…”
Section: Vbr 3 Monolayermentioning
confidence: 64%
“…1,[15][16][17][18] It is worth noting that FM CrI 3 , with a closed Cr 3+ t 3 2g shell, has a quenched orbital moment, and that its magnetic anisotropy comes from an exchange anisotropy induced by the spin-orbit coupling (SOC) of the heavy I 5p orbitals and their hybridization with Cr 3d. 19,20 In contrast, the open V 3+ t 2 2g shell in vanadium trihalides may carry an unquenched orbital moment and achieve a single ion anisotropy (SIA) via the V 3+ SOC. This seems to account for the hard perpendicular FM with T C ≈50 K observed in VI 3 bulk [16][17][18] and even the Ising FM in VI 3 monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spin-singlet p-wave MoS 2 introduces a new topological phase by broken time-reversal symmetry which is because of the spin-orbit interaction effect [14]. Recent studies reported s-wave and p-wave pairing superconducting states for graphene nanoribbons and investigated the topological states by Zak phase [15,16].…”
Section: Introductionmentioning
confidence: 99%